Drótháló 5. adás
1. Election campaigns: EKgP elections rally Jászberény 22 April, Agrárszövetség family Sunday Budapest, Almássy tér Recreation Center 23 April, MIÉP elections rally Budapest 23 April, MDF elections rally Siklós 23 April, Fidesz elections rally Budapest 23 April, Munkáspárt elections rally Budakeszi 23 April, MSZP elections rally Jászberény 24 April, SZDSZ economic forum Budapest 24 April, Köztársaság Párt elections rally Pilisvörösvár 24 April, KDNP elections rally Gyál 25 April. 2. Discussion with candidate ministers of finance: debts, state finances, foreign capital, import, export.